2015
DOI: 10.1364/josab.32.002172
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a phase-sensitive heterodyne detector

Abstract: It is believed that the quantum behaviors of homodyne detectors and traditional heterodyne detectors can be fully understood in the context of the quantum theory of optical detection. According to the theory, a 3 dB extra quantum noise has been predicted in a traditional heterodyne detector, as a phase-insensitive device, due to the existence of the image sideband vacuum. However, regarding the noise performance of a phase-sensitive heterodyne detector, a fundamental dilemma inevitably arises: On one hand, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 30 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Early studies were focused on the unbalanced homodyne and heterodyne [4,11], and later shifted to the balanced ones [12][13][14][15] for the advantageous suppression of the local oscillator (LO) excess noise. Since the above monochromatic-LO heterodyne has extra 3 dB noise compared to the homodyne [16] due to the vacuum fluctuation of the image band field [17], the bichromatic-LO heterodyne was proposed and proven to be free of this noise theoretically [9,16,18] and experimentally [19]. This scheme has recently been applied to detection of the broadband quadrature squeezing [20] and to the heterodyne readout in gravitational-wave detectors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies were focused on the unbalanced homodyne and heterodyne [4,11], and later shifted to the balanced ones [12][13][14][15] for the advantageous suppression of the local oscillator (LO) excess noise. Since the above monochromatic-LO heterodyne has extra 3 dB noise compared to the homodyne [16] due to the vacuum fluctuation of the image band field [17], the bichromatic-LO heterodyne was proposed and proven to be free of this noise theoretically [9,16,18] and experimentally [19]. This scheme has recently been applied to detection of the broadband quadrature squeezing [20] and to the heterodyne readout in gravitational-wave detectors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Is there a way to evade the fundamental quantum noise penalty with a heterodyne readout? It was found that the noise penalty of a heterodyne readout could be evaded if the image vacuum fields can be excited to contain coherent signal flux [14,22,23]. Inspired by this finding, we give a new gravitational wave detector scheme that includes two carriers at ω 1 and ω 2 with a beam at ω L ¼ ðω 1 þ ω 2 Þ=2 serving as the heterodyne LO.…”
mentioning
confidence: 95%